2018
DOI: 10.1038/s41467-018-06022-6
|View full text |Cite
|
Sign up to set email alerts
|

Conditional and interaction gene-set analysis reveals novel functional pathways for blood pressure

Abstract: Gene-set analysis provides insight into which functional and biological properties of genes are aetiologically relevant for a particular phenotype. But genes have multiple properties, and these properties are often correlated across genes. This can cause confounding in a gene-set analysis, because one property may be statistically associated even if biologically irrelevant to the phenotype, by being correlated with gene properties that are relevant. To address this issue we present a novel conditional and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 41 publications
(48 reference statements)
0
70
0
Order By: Relevance
“…Pairwise conditional gene set analysis allows one to disentangle overlapping associations of gene sets (see Methods). Conditional gene-set analyses can be used to examine whether a gene set is independently associated with a trait, rather than being associated because it is nested within a larger associated gene set 38 . These analyses indicated that nine gene sets constitute largely independent associations, defined as remaining significant in the majority of the conditional analyses ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Pairwise conditional gene set analysis allows one to disentangle overlapping associations of gene sets (see Methods). Conditional gene-set analyses can be used to examine whether a gene set is independently associated with a trait, rather than being associated because it is nested within a larger associated gene set 38 . These analyses indicated that nine gene sets constitute largely independent associations, defined as remaining significant in the majority of the conditional analyses ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Suggestive associations of additional pathways (corrected p<0.1), also implicated synaptic, potassium channel, and ionotropic pathways. To account for some genes appearing in multiple associated pathways, we conducted a conditional gene-set analysis accounting for overlap in genes amongst the top pathways 30 (excluding the Gene Ontology 31,32 [GO] terms "synapse," "GABA A gene," and "voltage-gated potassium channel" pathways due to multicollinearity). Results indicated that the GO "GABA receptor complex" and "regulation of synapse structure or activity" pathways were associated with cEF over and above other discovered pathways.…”
Section: Genetic Associations With Cef Implicate Gabaergic and Synaptmentioning
confidence: 99%
“…If this set of genes is enriched for strong statistical associations with a trait of interest, traditional GSA testing will result in significant associations for the "vesicle docking" and the "expressed in brain tissue" gene sets, unable to tell which of these is the most likely causal factor. Conditional GSA testing (94) addresses this issue by evaluating the evidence of association of one set (e.g., "vesicle docking") versus or in combination with another set (e.g., "expressed in brain tissue"). Such post hoc GSA testing has been shown to refine hypotheses on where convergence of polygenic signal resides (95), which is of crucial importance for designing meaningful functional follow-up experiments.…”
Section: Tools For Systematic Evaluation Of Convergence Of Trait-assomentioning
confidence: 99%